Performance of an optical readout GEM-based TPC - Margato, L. M. S. (2004)
We report on the operation of a GEM-based small TPC using an optical readout. The detector was operated with a mixture of Ar+CF4 using 5.48 MeV alpha particles obtained from a 241Am source and the GEM scintillation was concurrently read by a CCD camera and a photomultiplier. Precision collimators were used to define the track orientation. Qualitative results on the accuracy of the track angle, length and charge deposition measurements are presented.